Capital intelectual versus capital cultural científico no campo acadêmico da Educação física - LOBATO, Antonino Cezar Leite (Universidade Federal do Pará, 2017)
The main purpose of this research aimed to anlyze the epistemological space in which to set up the Scientific Field of Physical Education area in Brazil from the academic production from the Graduate Programs inherent to it. How to setup and features the intellectual and scientific capital in the academic production from the field of Physical Education in Brazil? How high-level qualification of which are invested teachers of higher education graduates with master's and doctorate is an intellectual capital able to generate and consolidate the production of scientific cultural capital in the Field of Physical Education area? As this phenomenon is metamorphosed in the strategies and disputes over intellectual productivity among the agents that make up the faculty that operates in Scientific Field of Graduate Programs in Physical Education, ranked by CAPES with notes 3, 4, 5 and 6? How intellectual capital acquired with the high-level training is transformed into scientific cultural capital can enhance the generation of knowledge in this field? The study was based on bibliographic and documentary analysis with theoretical foundation in the field of concept proposed by Pierre Bourdieu. I have chosen as a historical period to study object of analysis the 2003-2013 interval. Despite being late and have intensified since the 2000s the construction of the Field of Physical Education in Graduate Programs, the production of intellectual capital has expanded, however, between the programs classified by CAPES with notes 3, 4, 5 and 6, this dynamic is makes up amid the epistemological crisis and asymmetrically in terms of the generation of scientific cultural capital, ie the high-level training, does not guarantee that the researcher perform and contribute to the production of knowledge your area and this does not occur uniformly. Therefore, this phenomenon triggers the formation of zones of tension between intellectual capital and scientific cultural capital, since its agents start to adopt different strategies to design the academic field through the production that can bring together, in different application interstices triennial reviews and supported in the established rules.